2006
DOI: 10.1002/hec.1160
|View full text |Cite
|
Sign up to set email alerts
|

The effects of Taiwan's National Health Insurance on access and health status of the elderly

Abstract: The primary objective of this paper is to evaluate the impact of Taiwan's National Health Insurance program (NHI), established in 1995, on improving elderly access to care and health status. Further, we estimate the extent to which NHI reduces gaps in access and health across income groups. Using data from a longitudinal survey, we adopt a difference-in-difference methodology to estimate the causal effect of Taiwan's NHI. Our results show that Taiwan's NHI has significantly increased utilization of both outpat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
106
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 165 publications
(121 citation statements)
references
References 47 publications
13
106
2
Order By: Relevance
“…As shown, NHI increases the probability of having outpatient visits by 14.4 points for the previously uninsured elderly relative to the continuously insured elderly. In fact, this finding is similar to Chen et al (2007), who also use the same data. But there seems to be almost no effect on pharmacy visits.…”
Section: Nhi Effect On Utilizationsupporting
confidence: 90%
“…As shown, NHI increases the probability of having outpatient visits by 14.4 points for the previously uninsured elderly relative to the continuously insured elderly. In fact, this finding is similar to Chen et al (2007), who also use the same data. But there seems to be almost no effect on pharmacy visits.…”
Section: Nhi Effect On Utilizationsupporting
confidence: 90%
“…For example, Lu and Hsiao (2003) found that Taiwanese people have equal access to health care. Chen et al (2007) obtained similar results and found an increased use of health services by estimating the extent to which the NHI policy reduces gaps in access. Recently, Kreng and Yang (2011) measured the horizontal equity of health care resource allocation according to Taiwan's NHI policy.…”
Section: Case Introductionsupporting
confidence: 66%
“…It is more relevant than evidence on the effects of health insurance obtained from marginal changes in coverage, even when this is obtained experimentally (Newhouse, 1993;Finkelstein et al, 2012), because supply-side responses can make the impact of a large scale expansion of coverage disproportionate to that of a small scale increase (Finkelstein, 2007;Kondo, Shigeoka, 2013). Evidence from a middle-income country that implemented universal coverage a decade ago is more relevant to emerging economies contemplating this step than is evidence from the experience of the US and Japan fifty years ago (Finkelstein, 2007;Finkelstein, McKnight, 2008;Kondo, Shigeoka, 2013), and even from Taiwan (Chen et al, 2007;Chou et al, 2011;Chang, 2012;Keng, Sheu, 2013) that implemented universal coverage in 1995 at a much higher level of income than that of Thailand in 2002. Our evidence is distinguished from that obtained from major expansions of health insurance in the middle income settings of Colombia and Mexico not only by geography and the lower income of Thailand, but also by the nature of the reform in Colombia, which offered a means-tested subsidy for the purchase of private insurance covering care at a restricted network of providers (Miller et al, 2012), and the nature of the evidence in Mexico, which comes from an experiment that offers only a ten-month window within which to identify the effect on treated individuals offered the opportunity to voluntarily enroll relative to controls (King et al, 2009;Barofsky, 2011).…”
Section: This Interpretation Has Important Implications For Internatimentioning
confidence: 99%